Influence of socioeconomic status on functional recovery after ARDS caused by SARS-CoV-2: a multicentre, observational study. Issue 4 (22nd April 2022) - Declercq, Pierre-Louis; Fournel, Isabelle; Demeyere, Matthieu; Ksiazek, Eléa; Meunier-Beillard, Nicolas; Rivière, Antoine; Clarot, Caroline; Maizel, Julien; Schnell, David; Plantefeve, Gaetan; Ampere, Alexandre; Daubin, Cédric; et al.
Abstract : Introduction: Prognosis of patients with COVID-19 depends on the severity of the pulmonary affection. The most severe cases may progress to acute respiratory distress syndrome (ARDS), which is associated with a risk of long-term repercussions on respiratory function and neuromuscular outcomes. The functional repercussions of severe forms of COVID-19 may have a major impact on quality of life, and impair the ability to return to work or exercise. Social inequalities in healthcare may influence prognosis, with socially vulnerable individuals more likely to develop severe forms of disease. We describe here the protocol for a prospective, multicentre study that aims to investigate the influence of social vulnerability on functional recovery in patients who were hospitalised in intensive care for ARDS caused by COVID-19. This study will also include an embedded qualitative study that aims to describe facilitators and barriers to compliance with rehabilitation, describe patients' health practices and identify social representations of health, disease and care. Methods and analysis: The "Functional Recovery From Acute Respiratory Distress Syndrome (ARDS) Due to COVID-19: Influence of Socio-Economic Status" (RECOVIDS) study is a mixed-methods, observational, multicentre cohort study performed during the routine follow-up of post-intensive care unit (ICU) functional recovery after ARDS. All patients admitted to a participating ICU for PCR-proven SARS-CoV-2 infection and who underwent chest CT scan at the initial phase AND who received respiratory support (mechanical or not) or high-flow nasal oxygen, AND had ARDS diagnosed by the Berlin criteria will be eligible. The primary outcome is the presence of lung sequelae at 6 months after ICU discharge, defined either by alterations on pulmonary function tests, oxygen desaturation during a standardised 6 min walk test or fibrosis-like pulmonary findings on chest CT. Patients will be considered to be socially disadvantaged if they have an "Evaluation de la Précarité et des Inégalités de santé dans les Centres d'Examen de Santé" (EPICES) score ≥30.17 at inclusion. Ethics and dissemination: The study protocol and the informed consent form were approved by an independent ethics committee (Comité de Protection des Personnes Sud Méditerranée II) on 10 July 2020 (2020-A02014-35). All patients will provide informed consent before participation. Findings will be published in peer-reviewed journals and presented at national and international congresses. Trial registration number: NCT04556513